Wearable sensor network for lower limb angle estimation in robotics applications - Andres L. Jutinico; Gustavo A. R. Rodriguez; Julian R. Rolando Camargo Lopez (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
In human-robot interaction, sensors are relevant in guaranteeing stability and high performance in real-time applications. Nonetheless, accuracy and portable sensors for robots usually have high costs and little flexibility to process signals with free software. Therefore, we propose a wearable sensor network to measure lower limb angular position in human-robot interaction systems. The methodology employed to achieve the aim consisted in implementing a wireless network using low-cost devices, verifying design requirements, and making a validation via a proof of concept. The requirements to design the network include low loss of information, real-time communication, and sensor fusion to estimate the angular position using a gyroscope and accelerometer. Hence, the sensor network developed has a client-server architecture based on ESP8266 microcontrollers. In addition, this network uses the standard 802.11 b/g/n to transmit angular velocity and acceleration measures. Furthermore, we implement the user datagram protocol (UDP) protocol to operate in real-time with a sample time of 10 ms. Finally, we implement a proof of concept to show the system’s effectiveness. Thus, we use the Kalman filter to estimate the angular position of the foot, shin, thigh, and hip. Results indicate that the implemented sensor network is suitable for real-time robotic applications.